Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.24953/turkjped.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the frequency of iron insufficiency among infants in a population in which routine iron supplementation is implemented

Abstract: Çullas-İlarslan NE, Günay F, İleri DT, Elhan AH, Ertem M, Arsan S. Investigation of the frequency of iron insufficiency among infants in a population in which routine iron supplementation is implemented. Turk J Pediatr 2018; 60: 22-31. Iron deficiency anemia (IDA) represents the most common cause of anemia worldwide. Because of potential irreversible neurodevelopmental impairment, its prevention during infancy is essential. We aimed to investigate the frequency of iron insufficiency among infants in a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…En relación con las actitudes encontradas en el estudio desarrollado en la India ( 11 ) y el Reino de Bahrein ( 9), más del 80% de las madres consideraba que la dieta resultaba suficiente para tratar la anemia, esto difiere con el 54,8% de padres encuestados los que manifestaban estar en desacuerdo frente a este enunciado; esta situación podría ser el resultado de la educación brindada durante la consejería nutricional, sesiones educativas y visitas domiciliarias. Referente a estar de acuerdo en suspender el tratamiento por causa de los efectos secundarios los porcentajes superan el 40%, a lo que conlleva a mejorar el proceso de educación, capacitación y vigilancia de las promotoras o agentes de salud y las madres, de tal manera que se brinde soluciones paliativas ante dichas situaciones ( 16,17 ).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En relación con las actitudes encontradas en el estudio desarrollado en la India ( 11 ) y el Reino de Bahrein ( 9), más del 80% de las madres consideraba que la dieta resultaba suficiente para tratar la anemia, esto difiere con el 54,8% de padres encuestados los que manifestaban estar en desacuerdo frente a este enunciado; esta situación podría ser el resultado de la educación brindada durante la consejería nutricional, sesiones educativas y visitas domiciliarias. Referente a estar de acuerdo en suspender el tratamiento por causa de los efectos secundarios los porcentajes superan el 40%, a lo que conlleva a mejorar el proceso de educación, capacitación y vigilancia de las promotoras o agentes de salud y las madres, de tal manera que se brinde soluciones paliativas ante dichas situaciones ( 16,17 ).…”
Section: Discussionunclassified
“…La categorización y evaluación de las variables tuvo las siguientes consideraciones: cada variable contempló la aplicación de 10 ítems; sobre el nivel de conocimientos, cada respuesta correcta obtenía un puntaje de 2, además de utilizar para la calificación final una escala vigesimal con clasificación de bueno (16)(17)(18)(19)(20), regular (11)(12)(13)(14)(15) y malo (0-10). Las actitudes eran medidas a través de una escala de Likert de 5 niveles, que iba desde Muy en desacuerdo a Muy de acuerdo, puntuado de manera ascendente de 1 a 5.…”
Section: Materiales Y Métodosunclassified
“…According to a study conducted by Yalçın et al(14), the proportion of children who did not use prophylactic oral iron support was 31.2%. In a study conducted by Ilarslan et al(15), the rate for the same parameter was 44.3%. Reasons for stopping prophylaxis were; because the family found it unnecessary (31.1%), neglect (26.6%), side effects (16.6%), taste disturbance (15.3%).…”
mentioning
confidence: 86%
“…Reasons for stopping prophylaxis were; because the family found it unnecessary (31.1%), neglect (26.6%), side effects (16.6%), taste disturbance (15.3%). Also, 6.3% were not informed by healthcare workers and 4.1% feared possible side effects indicated by their family members(15). Karapinar et al(16) found that iron prophylaxis was not initiated in 16% of children, 44.5% discontinued prophylaxis.…”
mentioning
confidence: 99%
“…[1] Recent studies indicate that the prevalence of anemia in children ranges from 7% to 24% in Türkiye. [2][3][4] Nutritional deficiency due to a diet low in iron is the primary cause of iron deficiency (ID). Other risk factors for ID include low birth weight, periods of rapid growth such as infancy, early introduction of cow's milk and solid foods, breastfeeding beyond six months without iron supplementation, the mother's low education level, and low socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%